2020
DOI: 10.1186/s12967-020-02229-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics-based screening of key genes for transformation of liver cirrhosis to hepatocellular carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is the most common type of liver tumour, and is closely related to liver cirrhosis. Previous studies have focussed on the pathogenesis of liver cirrhosis developing into HCC, but the molecular mechanism remains unclear. The aims of the present study were to identify key genes related to the transformation of cirrhosis into HCC, and explore the associated molecular mechanisms.Methods: GSE89377, GSE17548, GSE63898 and GSE54236 mRNA microarray datasets from Gene Expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 46 publications
2
38
0
Order By: Relevance
“…There are 500,000 new liver cancer cases worldwide due to hepatitis B, hepatitis C and alcoholic liver disease 3 . The mechanisms of the development and progression of hepatocellular carcinoma (HCC) are complicated and regulated genetically and epigenetically 4 - 6 . Although a huge progress has been made on the research of HCC 7 - 9 , there is only an elemental understanding of its molecular pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…There are 500,000 new liver cancer cases worldwide due to hepatitis B, hepatitis C and alcoholic liver disease 3 . The mechanisms of the development and progression of hepatocellular carcinoma (HCC) are complicated and regulated genetically and epigenetically 4 - 6 . Although a huge progress has been made on the research of HCC 7 - 9 , there is only an elemental understanding of its molecular pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…No single biomarker has adequate sensitivity or speci city for HCC diagnosis. More and more studies are beginning to notice the use of genome-wide expression analysis to predict and diagnose diseases [35,36]. Compared with the single-gene biomarker, our multiple-genes based risk score-related prediction model got high accuracy with high sensitivity and speci city, which could be also used in other studies.…”
Section: Disscusionmentioning
confidence: 94%
“…In a previous study utilizing bioinformatics-based screening, the upregulation of Cdkn3 was also identified as a marker of transformation from cirrhosis into HCC and correlated with the occurrence, invasion, and recurrence of HCC [50]. Akr7a3 [51], Cdc2a [50,52], and Cdkn3 [50] have also been found as biomarkers for early diagnosis, staging, and prognosis in human liver cancer clinically.…”
Section: Analysis Of the Time-invariant Biomarkersmentioning
confidence: 97%
“…More than 80% of HCC, the most common type of liver cancer, develops in fibrotic or cirrhotic livers, suggesting the importance of the two conditions in promoting liver cancer development [56]. Recently, many bioinformatics approaches have identified several key genes and pathways for transforming cirrhosis to HCC, and Akr7a3, Cdc2a, and Cdkn3 were identified by these studies [42,50,51]. There are some limitations to the study.…”
Section: Analysis Of the Time-invariant Biomarkersmentioning
confidence: 99%